Risk Factors Associated To The Occurrence Of Isolated Systolic Hypertension: A Literature Review - Nurjanah Nurjanah; Farapti Farapti (CV. AFDIFAL MAJU BERKAH, 2026)
Isolated systolic hypertension (ISH) is a growing public health concern, particularly among older adults, due to its strong association with cardiovascular morbidity and mortality. This study aims to identify and analyze risk factors associated with ISH. This research is a literature study, with sources obtained from three open-access journal databases: PubMed, Wiley Online Library, and Google Scholar. Articles were selected based on specific inclusion criteria, including full-text articles, published between 2015 and 2025, written in English, focused on ISH risk factors, and excluding literature reviews. The search resulted in 8 articles for review. Risk factors are typically classified into two categories: modifiable and non-modifiable. Modifiable risk factors include obesity, alcohol consumption, low educational level, elevated fasting blood sugar levels, employment, retirement status, and income. Conversely, non-modifiable risk factors consist of older age and male sex. Risk factors related to the incidence of ISH were found in all literature, namely age, gender, obesity, alcohol consumption, diabetes mellitus, low educational level, income, and socioeconomic status. The findings emphasize the importance of lifestyle modification and regular blood pressure monitoring for high-risk populations to prevent ISH.